Potensi Farmakologis Genus Chloranthus Sebagai Agen Antioksidan, Sitotoksik, Dan Anti-Inflamasi: Sebuah Tinjauan Sistematis - Wildan Firdaus, Muhammad; Haryoto, Haryoto (Journal of Pharmaceutical and Sciences, 2025)
The Chloranthus genus (Chloranthaceae family) has been traditionally used in Asian medicine as an anti-inflammatory agent, but recent scientific exploration reveals broader pharmacological potential. This systematic review aims to evaluate the latest experimental evidence on the antioxidant, cytotoxic, and anti-inflammatory activities of Chloranthus-derived compounds and elucidate their molecular mechanisms. Studies were selected through structured database searches using specific keyword combinations and screened using rigorous inclusion-exclusion criteria. The findings highlight a predominance of sesquiterpenoids, particularly lindenane-type (monomers, dimers, and trimers), which consistently exhibit anti-inflammatory effects via inhibition of NF-κB and MAPK pathways and modulation of the NLRP3 inflammasome. Antioxidant activity through the Nrf2/Keap1 pathway and cytotoxic effects against cancer cells were also frequently reported. Notably, several compounds demonstrated dual actions, suppressing both ROS (Reactive Oxygen Species) production and proinflammatory cytokines, emphasizing their relevance in treating diseases involving oxidative stress and inflammation. These results support Chloranthus as a promising natural source of multitarget bioactive compounds. Future research should adopt a multidisciplinary approach to further elucidate molecular targets, validate in vivo efficacy, and explore novel biological resources.